Optical and mechanical properties of long-term ordered semiconductors - Ballato, John (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
The 45-year-monitoring of optical and mechanical properties of the various semiconductor crystals grown in the sixties of the past century shows that the stimuli for long-term improvement of crystal quality prevail over those which lead to its degradation. Evolution of optical and mechanical properties testifies that now in diamond-like gallium phosphide (GaP) doped with nitrogen (N), the impurity is a regular element of the new crystal lattice - it increases the forbidden gap, and at relevant concentration and level of optical excitation creates a bound excitonic crystal. The ternary compound CdIn2S4, now having the perfect normal (instead of partly inversed) spinel crystal lattice, as well as GaP with evenly distributed impurities, demonstrate new stable and bright luminescent phenomena, including stimulated emission and “hot” luminescence at room temperature. All chosen semiconductor crystals from different groups of semiconductor compounds demonstrate the long term ordering and improvement of useful for application properties. Existing technologies help us to reproduce artificially these naturally ordered structures for application in optoelectronics.